Procedural structuralism? The semiotic square and the genesis of meaning - Barbieri, Daniele (E|C, 2020)
This paper organizes some considerations about the semiotic square, intended as articulation of the two categories, guessed as fundamental, of Alterity and Transformation. In this sense, the semiotic square would not only organize the deepest level of the generative path, but any operation of meaning. Since Transformation is an intimately temporal notion, understood in this sense the square would incorporate in itself, even at the deepest level, a temporal component even upstream of the preconversion, sketching a perspective of processual structuralism, in which the structure is located more at the level of parole, that is of use and genesis of meaning, than at the level of langue, that is of a deposited system.